From the divergence of senescent cell fates to mechanisms and selectivity of senolytic drugs. Issue 9 (21st September 2022) - L'Hôte, Valentin; Mann, Carl; Thuret, Jean-Yves
Abstract : Abstract : Senescence is a cellular stress response that involves prolonged cell survival, a quasi-irreversible proliferative arrest and a modification of the transcriptome that sometimes includes inflammatory gene expression. Senescent cells are resistant to apoptosis, and if not eliminated by the immune system they may accumulate and lead to chronic inflammation and tissue dysfunction. Senolytics are drugs that selectively induce cell death in senescent cells, but not in proliferative or quiescent cells, and they have proved a viable therapeutic approach in multiple mouse models of pathologies in which senescence is implicated. As the catalogue of senolytic compounds is expanding, novel survival strategies of senescent cells are uncovered, and variations in sensitivity to senolysis between different types of senescent cells emerge. We propose herein a mechanistic classification of senolytic drugs, based on the level at which they target senescent cells: directly disrupting BH3 protein networks that are reorganized upon senescence induction; downregulating survival-associated pathways essential to senescent cells; or modulating homeostatic processes whose regulation is challenged in senescence. With this approach, we highlight the important diversity of senescent cells in terms of physiology and pathways of apoptosis suppression, and we describe possible avenues for the development of more selective senolytics.